2021
DOI: 10.1101/2021.10.25.21265398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide polygenic score withAPOL1risk genotypes predicts chronic kidney disease across major continental ancestries

Abstract: Introduction: Chronic kidney disease (CKD) is a common complex condition associated with significant morbidity and mortality in the US and worldwide. Early detection is critical for effective prevention of kidney disease progression. Polygenic prediction of CKD could enhance screening and prevention of kidney disease progression, but this approach has not been optimized for risk prediction in ancestrally diverse populations. Methods: We developed and validated a genome-wide polygenic score (GPS) for CKD defin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…12 , Khan et al . 13 ) in the general population, little is known about the relationship of an eGFR PGS to adverse outcomes in persons with already diagnosed moderate CKD, a novel aspect addressed in this study. In agreement with our findings, a previous population-based study by Yu et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 , Khan et al . 13 ) in the general population, little is known about the relationship of an eGFR PGS to adverse outcomes in persons with already diagnosed moderate CKD, a novel aspect addressed in this study. In agreement with our findings, a previous population-based study by Yu et al .…”
Section: Discussionmentioning
confidence: 99%
“…While various studies focused primarily on the association of an eGFR PGS with clinical outcomes or the prediction of the presence of CKD (e.g. Yun et al 12 , Khan et al 13 ) in the general population, little is known about the relationship of an eGFR PGS to adverse outcomes in persons with already diagnosed moderate CKD, a novel aspect addressed in this study. In agreement with our findings, a previous population-based study by Yu et al 8 reported significant positive association of a similarly developed eGFR PGS with incident CKD and KF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies aiming to efficiently recruit appropriate subjects naturally focus on Black, African, and African-American populations, as well as other specific populations known to have significant recent west African ancestry. It may prove to be the case that other variants related to ancestry may affect the severity of APOL1-associated kidney disease, but the individual effects of these variants, if they exist, are small [97]. G1 and G2 behave differently from G0 in a variety of model systems that allow APOL1 genotypes to be isolated as the only variable [98].…”
Section: Issues Of Race and Ancestrymentioning
confidence: 99%